The sublime as a challenge to the conception of imitative art: the case of romantic poetry and painting - Silva Santos, Fabiano Rodrigo da [UNESP] (Univ Estadual Paulista, Fundacao Editora Unesp, 2023)
We intend to consider the relationships between the debate on the sublime, which has as its relevant point the aesthetic thought of the 18th century, and the development of a poetic of ellipsis, suggestion and transfiguration of world impressions in the painting and poetry of the 191h century. We intend to discuss the association between the idea of the sublime and the recognition of the crisis of figurative art and its poetic corollary, discursive poetry, in artistic manifestations of the romantic tradition. In this way, the sublime is treated as an aesthetic idea that encompasses experiences of art and sensibility that convert the need to transcend the means of expression into a motivating element of artistic performance of a certain tendency in Romantic poetry and painting. This tendency is present in creations that reflect modern poetics, particularly those that are sensitive to the negative and crisis elements that surround artistic expression and that manifest the self-consciousness that responds to these elements.
Keywords: Sublime; Romanticism; Relations between poetry and painting